Dampak Penundaan Pembagian Harta Warisan Di Kecamatan Kota Jantho Kabupaten Aceh Besar - Tarmizi M Jakfar; Gamal Achyar; Dinda Farina Rizqy (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2022)
Inheritance is a science that studies the process or method of transferring the heirs' (deceased) property to their heirs and how much each heir gets. As is known, inheritance is an asset that is distributed after the owner dies. Inheritance is one of the problems that is very influential in everyday life; if the inheritance cannot be shared among families, there will be quarrels between families. The questions in this thesis are the reasons for the delay in the distribution of inheritance in the Jantho District, Aceh Besar District, the impact of the delay in the distribution of inheritance in the Jantho City District, Aceh Besar District, and a review of Islamic law delaying the distribution of inheritance in the Jantho District, Aceh Besar District. In this research, the author uses field research methods and library research methods using interview techniques. The results of the study The reasons behind the delay in the distribution of inheritance in the District of Jantho City, Aceh Besar Regency, are three, namely: the agreement of the heirs to delay the distribution of the inheritance; the heirs are still small or have not been able to manage the inheritance; and discussing the inheritance after the heir dies. Death is considered taboo by some people. The reasons behind the delay in the distribution of inheritance in the Kota Jantho sub-district, Aceh Besar district, are as follows: the breakdown of friendship between the heirs; the change in the status of the inheritance to private land; and the occurrence of disputes between families. In Islamic law, delaying the distribution of inheritance is not recommended; however, the postponement may be done for certain reasons or with syar'i udzur and with the approval of other heirs. However, if the delay in the distribution of inheritance is carried out for years, it will certainly cause problems in the future.